The length of skin incision and the ability of surgeon - Fiorelli, Alfonso; Santini, Mario (Video-Assisted Thoracic Surgery; Vol 1 (October 2016): Video-Assisted Thoracic Surgery, 2016)
Thoracotomy is one of the most painful incision and an non adequate control of post-thoracotomy pain increases the morbidity and mortality (1,2). Despite post-thoracotomy pain has different sources, reducing skin and chest wall incision with minimally invasive approaches could decrease the pain stimuli and improve the postoperative outcome. In the last two decades, video-assisted thoracoscopic surgery (VATS) has emerged as alternative strategy to standard open thoracotomy in the management of lung, chest wall, mediastinal and pleural diseases (3-10). Benefits of VATS over thoracotomy include less postoperative pain, shorter hospital stay, less morbidity and mortality, better cosmetic results and similar oncological outcome. Thus, VATS has become the treatment of choice in elderly patients with severe comorbidity and/or in young patient with poor clinical conditions that cannot tolerate the surgical trauma of thoracotomy (11-14).